Impact of physical distance and psychological distress on job turnover intention among front-line health workers during COVID-19 pandemic - Haque, A. K. M. Ahasanul; Tarofder, Arun Kumar; ., Noor Hazilah; ., Farzana Yasmin; Rehman, Shabina; Sarker, Md Atiqur Rahman; Kabir, Sardar Md Humayun (Sichuan Institute of Piezoelectric and Acoustooptic Technology, 2021)
COVID-19 pandemic compels strict isolation to avoid the spread of Coronavirus. Physical distance with COVID-19 patients is undeniable for font-line health workers. This physical proximity of doctors and nurses at hospital affects their mental health and generating psychological distress. They sacrifice their social life and keeping themselves isolated due to their regular contact with COVID-19 patients. This causes high rate of depression, anxiety and stress. Therefore, this study aims to identify the effect of physical distancing and psychological distress on job turnover intention among the front line health workers. This study is applying Protection Motivation Theory (PMT) to understand this relationship. Data has been collected between March and April 2021 through structured questionnaire from doctors, nurses and hospital staffs who are managing COVID-19 patients at hospitals. This research has discovered that as front-line health workers' fear of COVID-19 grows, so does their relational anxiety, as well as their organizational and technical turnover intentions. Therefore, there is a need of psychological assistance and increasing capacity building for the front-line workers. This study includes only two variables to understand job turnover intention. For more insights and understanding of the experience in the light of COVID-19, further study can be done by including other factors like institutional support, policy implementation and social dilemma.